A STUDY ON FACTORS AFFECTING OVERALL JOB SATISFACTION AND TURNOVER INTENTION: SPECIAL REFERENCE IN INSURANCE SECTOR (International Journal of Food and Nutritional Sciences, 2023)
The purpose of this study is to evaluate the degree of job satisfaction and how it relates to the intention of turnover in Uttar Pradesh Insurance companies. 400 questionnaires were circulated to Insurance employees among these 393 are valid. Results shows employees of Insurance companies are dissatisfied or leave the organization if these factors are like Organizational Policies and strategies, Working environment, Compensation level, career development and supervision are absent It was demonstrated that each indicator of work satisfaction and the intention to leave were significantly correlated. It was concluded that the intention to leave and job satisfaction were significantly correlated negatively.